THE EFFECT OF 3-2-1 TECHNIQUE AND READING MOTIVATION TOWARD STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT GRADE XI IPA OF SMAN 1 BANGKINANG SEBERANG - Citra Ayu (Journal of English Language and Education, 2016)
This study describes and concluded that the existence of teaching reading narrative texts for high school students using varied techniques have touched the substantive area. 3-2-1 techniques are cooperative learning techniques have been reconstructing the individual instruction that has been applied in schools. The purpose of this study was to determine the effect of learning techniques and reading motivation of students to learn English results. This research used experimental method with 2x2 factorial design and conducted in SMAN 1 Bangkinang Opposite, Riau with a sample of 2 classes. Results of the analysis of the data reveals that: (a) students who are taught by the 3-2-1 technique showed better results than students taught using conventional techniques, (b) students who have high motivation techniques taught by 3-2- 1 shows the results of the study as well as students who are taught by using conventional techniques, (c) students who have low motivation taught using 3-2-1 techniques showed better learning outcomes than students taught using techniques conventional, and (d) there is interaction between the use of techniques learned by the students' reading motivation. However, the results of different values between the experimental group with the control group to measure achievement in this study that the 3-2-1 technique has a better effect than with conventional techniques. On the other hand, students 'reading motivation affect students' reading results.